Vehicle Safety Enhancement System: Sensing and Communication. (29th December 2013) - Qian, Huihuan; Chen, Yongquan; Sun, Yuandong; Liu, Niansheng; Ding, Ning; Xu, Yangsheng; Xu, Guoqing; Tang, Yunjian; Yan, Jingyu
With the substantial increase of vehicles on road, driving safety and transportation efficiency have become increasingly concerned focus from drivers, passengers, and governments. Wireless networks constructed by vehicles and infrastructures provide abundant information to share for the sake of both enhanced safety and network efficiency. This paper presents the systematic research to enhance the vehicle safety by wireless communication, in the aspects of information acquisition through vehicle sensing, vehicle-to-vehicle (V2V) routing protocol for the highly dynamic vehicle network, vehicle-to-infrastructure (V2I) routing protocol for a tradeoff in real-time performance and load balance, and hardware implementation of V2V system with on-road test. Simulations and experimental result validate the feasibility of the algorithms and communication system.